2018
DOI: 10.4314/gmj.v52i4.6
|View full text |Cite
|
Sign up to set email alerts
|

Capacity for providing caesarean section services in selected health centres and district hospitals in Tanzania

Abstract: Objective: Tanzania has a high maternal mortality ratio of 556 per 100,000 live births. Timely caesarean sections avert mortality due to life threatening conditions like obstructed labour. This study assessed capacity of selected health facilities to provide caesarean sections in terms of infrastructure, equipment, essential supplies and skill mix. Methods: A cross-sectional mixed methods design was used to include systematic observations using highly structured checklists to determine the adequacy of infrastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…In Tanzania, the safety of caesarean sections performed by assistant medical officers and medical doctors was not significantly different, based on maternal mortality, maternal complications and early neonatal mortality measures. However, Matinhure et al. (2018) did highlight that physicians were significantly more likely to perform emergency deliveries [odds ratio (OR) 2.52, 1.80–3.53].…”
Section: Resultsmentioning
confidence: 99%
“…In Tanzania, the safety of caesarean sections performed by assistant medical officers and medical doctors was not significantly different, based on maternal mortality, maternal complications and early neonatal mortality measures. However, Matinhure et al. (2018) did highlight that physicians were significantly more likely to perform emergency deliveries [odds ratio (OR) 2.52, 1.80–3.53].…”
Section: Resultsmentioning
confidence: 99%
“…Unavailability of prescribed medication means that the hospital has to outsource from another, thus contributing to more complications (Mokoena, 2017). Matinhure et al (2018) found that a lack of obstetric resuscitation equipment delayed essential care for women in labour. Malelelo-Ndou et al (2019) revealed that certain drugs were requested from other hospitals which resulted in late administration.…”
Section: Negative Impact Of the Shortage Of Resources On Patientsmentioning
confidence: 99%